2020
DOI: 10.1186/s43055-020-00313-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of diffusion-weighted MRI in characterization of mediastinal masses

Abstract: Background Diffusion MR imaging (DWI) is a widely available non-invasive non-contrast functional MR imaging technique with short acquisition time. It helps in the analysis of tissue characteristics based on the diffusion of water protons within the tissue. Quantitative assessment of a mass is possible by calculating its apparent diffusion coefficient (ADC) value which is inversely correlated with tissue cellularity. So, DWI has diagnostic potential to distinguish benign from malignant tumors because of the ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(38 reference statements)
2
1
0
Order By: Relevance
“…When using the hot-spot approach, the mean ADC to distinguish malignant from benign tumors was 1.17 x10 -3 mm 2 /s, with the area under curve ROC was 0.794, sensitivity and specificity were 80%. This result is concordant with that of Raafat et al who revealed that the cut-off ADC value for the differentiation between malignant and benign mediastinal lesions was 1.11 x10 -3 mm 2 /s, with sensitivity of 90.9% and specificity of 100% [10]. However, our result is discordant with Usuda et al, who reported higher cut-off value of 2.21 x10 -3 mm 2 /s for the discrimination between malignant and benign mediastinal tumors [11].…”
Section: Discussionsupporting
confidence: 92%
“…When using the hot-spot approach, the mean ADC to distinguish malignant from benign tumors was 1.17 x10 -3 mm 2 /s, with the area under curve ROC was 0.794, sensitivity and specificity were 80%. This result is concordant with that of Raafat et al who revealed that the cut-off ADC value for the differentiation between malignant and benign mediastinal lesions was 1.11 x10 -3 mm 2 /s, with sensitivity of 90.9% and specificity of 100% [10]. However, our result is discordant with Usuda et al, who reported higher cut-off value of 2.21 x10 -3 mm 2 /s for the discrimination between malignant and benign mediastinal tumors [11].…”
Section: Discussionsupporting
confidence: 92%
“…This result is concordant with that of Raafat et al. who reported that the cutoff ADC value for the differentiation between malignant and benign mediastinal lesions was 1.11 x 10 -3 mm 2 /sec, with sensitivity of 90.9% and specificity of 100% ( 5 ). However, our result is discordant with the work of Usuda, who reported a higher cutoff value of 2.21 x 10 -3 mm 2 /sec for discriminating between malignant and benign mediastinal tumors ( 6 ).…”
Section: Discussionsupporting
confidence: 92%
“…The knowledge regarding MRI features of these masses is still considered to be modest because of their paucity. There have been published studies on the role of MRI in evaluating anterior mediastinal masses, some of which stressed the value of DWI in differentiating benign lesions and malignancies ( 5 , 6 ). Yet only a few studies tried various approaches to obtain the ADCs or to group the lesions.…”
Section: Introductionmentioning
confidence: 99%